Green synthesis of rGO/MgO nanocomposite using Hylocereus polyrhizuspeel extract for antibacterial activity and photocatalytic dye degradation study - Sunil Kumar Abel; Saranya Amirtharajan; Arulprakasajothi Mahalingam; Srimanickam Baskaran; Sakthivel Pandurengan (Chemical Physics Impact)
Current study demonstrates the preparation of rGO/MgO nanocomposite using Hylocereus polyrhizus due to its functional benefits, and green strategy method. Scanning electron microscopy (SEM) with Energy Dispersive X-ray analysis and X-ray diffraction were used to find the presence of crystal structure and the elemental analysis. XRD results revealed the cubic structure of the synthesized nanocomposite. The average crystallite size was 36.16 nm. The SEM portrays the agglomerated granular structure has larger scale web like structure are highly interconnected with large voids. The presence of graphene, magnesium and oxygen were analysed from the EDAX elemental studies. The presence of MgO and rGO diffraction planes is well matches with JCPDS card no. 04-0829 and 75-2078. Mg–O–C stretching vibrations and C–O stretching vibrations reflected from FTIR studies confirms the presence of Mg and C in prepared composite. Furthermore, the photocatalytic capability of green synthesized rGO/MgO nanocomposite were employed to investigate the Methylene Blue degradation under solar irradiation when exposed to sunlight for 90 min, about 93 % of the dye was degraded. Disc diffusion method was performed to test the antibacterial activity against S. aureus and Escherichia coli at higher concentration of nanocomposite reveals that S. aureus showed maximum zone of inhibition. rGO/MgO material in terms of bioremediation of domestic and industrial waste by killing pathogenic bacteria, breaking down of colourant. The rGO/MgO nanocomposite's promise in environmental remediation is demonstrated by these results, especially in wastewater treatment for dye degradation and harmful bacteria suppression.